Sebastes oculatus, Patagonian Rockfish - Buratti, C. (2020)
This demersal, reef-associated species is common and abundant through much of its range. It is taken in fisheries at relatively low levels and may be impacted by invasive salmon. Global-level declines are not considered to be approaching a Near Threatened or threatened level at this time; therefore, it is listed as Least Concern.